Fiscal policy and real interest rates - Francesco Bianchi; Renato Faccini; Leonardo Melosi (Danmarks Nationalbank, 2024)
We employ a new class of general equilibrium models with partially unfunded debt, as proposed in Bianchi et al. (2023), to study the relation between real interest rates and fiscal policy. Unfunded fiscal shocks generate a decline in real interest rates, while funded fiscal shocks cause an increase. We use the model to assess the historical path of real interest rates in the United States, traditionally a key driver of international real interest rates. We find that the fiscal real interest rate, defined as the component of the real rate related to unfunded fiscal shocks, accounts for a large share of the low-frequency movements in real interest rates. This suggests that fiscal policy will play a key role in determining the future path of real interest rates.
Keywords: E50; E62; E30; 330; Unfunded fiscal spending; persistent inflation; large public debt; inflation risk; shock-specific rule